Evaporation of nanofluid sessile drops: Infrared and acoustic methods to track the dynamic deposition of copper oxide nanoparticles. (December 2018) - Zaaroura, Ibrahim; Toubal, Malika; Reda, Hilal; Carlier, Julien; Harmand, Souad; Boukherroub, Rabah; Fasquelle, Aurélie; Nongaillard, Bertrand
Highlights: Nanofluids represent a new and innovative class of heat transfer fluids with potential applications in various fields such as coolants in the automobile, electronics, fuel cells, etc. Nanofluids are engineered by dispersing nanometer-sized solid particles in conventional heat transfer fluids. Thermal conductivity of a nanofluid could be enhanced compared to pure liquid after the addition of nanoparticles that increase the heat transfer in the systems. Many studies were performed to analyze and observe the evaporation process of nanofluid sessile droplets and to visualize the final shape pattern of nanoparticles due to change in surface temperature, but without monitoring the time at which nanoparticles start to deposit on the surface during the evaporation process. Monitoring of nanoparticle dynamic deposition was performed using the infrared and acoustic method during the evaporation process. These two methods give a clear analysis of the behavior of the droplet at the liquid-air and solid-liquid interfaces. Moreover, an estimate of the particles concentration throughout the process was deduced. Abstract: In this work, we investigated the precipitation of 0.05%wt copper oxide nanoparticles in a sessile droplet during the evaporation process. We used two complementary methods to analyze the precipitation process of the nanoparticles at the solid/liquid interface: an optical one coupled to an infrared thermography method and an acoustic method. From the optical observation, using a Keyence microscope on the rear side of a transparent glass substrate coated with a silane layer, the precipitation process of the nanoparticles was successfully monitored by measuring the mean intensity density ( ID ‾ ) above the substrate by using ImageJ software. The acoustic method, based on a high frequency echography principle, allowed to monitor the deposition phenomenon of the particles above a non-transparent silicon substrate having similar silane coating as the glass substrate at room temperature. The time from which the nanoparticles begin to settle at the bottom of the substrate, obtained from the acoustic method, corroborated the one obtained from the optical one. Moreover, an estimate of the particles concentration throughout the process was deduced. The effect of substrate temperature and substrate wettability have also been studied experimentally and investigated using only the optical method and the infrared thermography one. An infrared camera from the top was employed to observe the temperature effect on the precipitation of the nanoparticles. Furthermore, when the substrate temperature exceeded 60 °C, co-existence of the thermal Marangoni flows was observed. It is expressed as a temperature gradient at the droplet liquid/air interfaces. The result showed the effect of these cells due to Marangoni effect on the nanoparticles' stability.